BASIC CONCEPTS ALGORITHM AND THREE DIMENSIONAL IMAGE PROCESSING - Budi Kusnoto; Ir. Oon Amroni. Msc (Jurnal Sistem Komputer, 1993)
Algorithm development of three-dimensional process itself, of course, is the most important thing that should always be considered. Given that the processes that occur within a three-dimensional graph is not a simple process, further errors in the determination or selection of a three-dimensional algorithm to perform a specific job can result in swelling of the use of processing time or even cause the error output of three-dimensional graphics that are not expected. Understanding of basic concepts and algorithms used in the techniques of three-dimensional graphics processing plays a very important as a guide to choosing the appropriate algorithm in a specific three-dimensional process. Share kinds of algorithms have been developed and therefore the selection of an appropriate algorithm for a particular issue a great effect on the performance of a system of three- dimensional graphics. It is expected that with the writing of this it can be helpful in determining an algorithm for a particular process, and it is possible to develop other algorithms are more effective and efficient.